2014
DOI: 10.1088/0031-9155/59/20/6031
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation in cancer therapy without insertion of electrodes

Abstract: Electroporation in cancer therapy in which elongated micron-sized conductors are used to enhance an externally applied electric field is investigated. Such field enhancement was previously used in carbon and boron nitride nanotube electropermeabilization. It is envisaged that the micro-conductors would be injected together with therapeutic drugs into tumorous regions, and a pulsed or alternating external field would be applied. Amplification of this external electric field at the pointed ends of the elongated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The reported results show that the electric field distribution and the consequent transmembrane voltage are influenced by the intracell material conductivity (named the stroma), σS, the cell interior conductivity, σC, and in some cases the cell distance and non-homogeneous stroma arrangement. From the color map of the electric field strength, it can be observed, as is well known, e.g., in [30,52], that the cells are able to locally modify the electric field strength distribution even if the stroma conductivity is homogeneous in all the domains (Figure 3A-D). The cells shown in Figure 3 have a cell diameter of 50 µm and a density of 9 cell/mm 2 with a cell-cell distance of 283 µm for the cases in panels A, B, and E and a density of 350 cell/mm 2 with a cell-cell distance of 3.5 µm for the cases in panels C and D. Figure 3 compares, in terms of electric field distribution (color map), electric potential along α (x-axis in the reported behavior) and transmembrane potential, in the cases of well-separated cells and aggregated cells.…”
Section: Numerical Analysis Of Relevant Casesmentioning
confidence: 58%
“…The reported results show that the electric field distribution and the consequent transmembrane voltage are influenced by the intracell material conductivity (named the stroma), σS, the cell interior conductivity, σC, and in some cases the cell distance and non-homogeneous stroma arrangement. From the color map of the electric field strength, it can be observed, as is well known, e.g., in [30,52], that the cells are able to locally modify the electric field strength distribution even if the stroma conductivity is homogeneous in all the domains (Figure 3A-D). The cells shown in Figure 3 have a cell diameter of 50 µm and a density of 9 cell/mm 2 with a cell-cell distance of 283 µm for the cases in panels A, B, and E and a density of 350 cell/mm 2 with a cell-cell distance of 3.5 µm for the cases in panels C and D. Figure 3 compares, in terms of electric field distribution (color map), electric potential along α (x-axis in the reported behavior) and transmembrane potential, in the cases of well-separated cells and aggregated cells.…”
Section: Numerical Analysis Of Relevant Casesmentioning
confidence: 58%
“…It is also agreed that a combination of nanoparticle-based gene therapy with a drug, radiotherapy, photodynamic therapy, immunotherapy, or others will be emphasized in future clinical studies [37]. In the context of electroporation, the theoretical model predicting the potential of the use of conductive nanoparticles emerged and was proposed by Lekner [38] and Qiu et al [39]. It was shown that the conductive nanoparticles in close proximity to the membrane are capable of increasing the electric field and increasing the density of the hydrophilic pores.…”
Section: Introductionmentioning
confidence: 99%
“…La aplicación de una fuerte estimulación eléctrica da como resultado un mayor potencial transmembrana que podría formar poros en la membrana celular. Estos poros reversibles podrían durar un tiempo específico, durante el cual las células podrían repararse (Gintautas 1997) y las biomoléculas difundirse o derivarse por la fuerte fuerza electroforética en la región objetivo (Pei-Chi 2016;Lekner 2014;Neumann 1999).…”
Section: Introductionunclassified